Review of the Indian Ocean spikefish genus Mephisto (Tetraodontiformes: Triacanthodidae) - Bemis, Katherine E.; Tyler, James C.; Psomadakis, Peter N.; Ferris, Lauren Newell; Kumar, Appukuttannair Biju (Zootaxa, 2020)
We redescribe the triacanthodid spikefish Mephisto fraserbrunneri Tyler 1966 based upon eight specimens (five newly reported herein) and the first color photographs of freshly collected specimens; these data are compared with that of the single specimen of the recently described M. albomaculosus Matsuura, Psomadakis, and Mya Than Tun 2018. Both species are found in the Indian Ocean, with M. fraserbrunneri known from the Arabian Sea off the east coast of Africa to the eastern Bay of Bengal, and M. albomaculosus confirmed only from the type locality in the Andaman Sea (a color photograph of an individual M. cf. albomaculosus from the Bay of Bengal that was not retained is also presented). We describe and diagnose the genus Mephisto and provide a key to the two species based upon all available specimens. We also provide a distribution map for both species and summarize literature records. Using micro-CT data, we show that Mephisto fraserbrunneri replaces teeth intraosseously, which suggests this tooth replacement pattern is plesiomorphic for Tetraodontiformes.